ANALISIS KESULITAN SISWA DALAM PENDEKATAN DEEP LEARNING BERDASARKAN PENGALAMAN BELAJAR DI SMK NEGERI 1 BANJARMASIN - Nijmiyatillail; Nor, Baseran; Puteri Amima, Sharfina; Atmono, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of 21st-century learning requires students to not only under-stand knowledge conceptually, but also to be able to digest, apply, and reflect onthat knowledge well. One method that supports this goal is immersive learning. How-ever, in practice, there are still various learning difficulties that can affect studentsuccess in the learning process. This study aims to analyze the implementation ofimmersive learning, student learning difficulties, and student learning experiencesin the Creative Project and Entrepreneurship (PKK) subject at SMK Negeri 1 Ban-jarmasin. The method used in this study is a descriptive quantitative approach. Thepopulation in this study consisted of 1,561 students with a sample of 310 studentstaking using the Krejcie and Morgan formula and purposive random sampling tech-nique. Data were collected through a questionnaire using a Likert scale. Data anal-ysis was carried out by calculating respondent scores, average values (mean), per-centages, and categories. The results showed that the implementation of immersivelearning was in the high category with the highest indicator in the metacognitionaspect. Student learning difficulties are influenced by internal and external factors,with student health being the most significant internal factor and the learning envi-ronment being the most influential external factor. Student learning experiences arecategorized as high, with reflection as the most dominant aspect. Research findingsindicate that positive learning experiences contribute to the implementation of deeplearning, although several challenges remain to improve learning quality.